Bimetallic metal-organic framework derived Sn-based nanocomposites for high-performance lithium storage. (10th November 2019) - Xu, Keqiang; Ma, Lianbo; Shen, Xiaoping; Ji, Zhenyuan; Yuan, Aihua; Kong, Lirong; Zhu, Guoxing; Zhu, Jun
Abstract: Sn-based materials as potential anode materials have triggered significant research interests for lithium storage owing to their high theoretical capacity and low cost. However, the practical applications of Sn-based materials are hindered by low capacity release and fast capacity fading due to large volume expansion and structural pulverization of the electrodes during cycling. Herein, we demonstrate an efficient strategy to alleviate/resolve the above issues by introducing highly conductive inactive metal to alloy with Sn and then loading the Sn-based alloy particles onto two-dimensional (2D) graphene matrix. The graphene supported Fe–Sn nanoalloy composites (FeSn2 /FeSn/Fe-rGO) are synthesized via a facile bimetallic metal-organic framework precursor route, in which Sn3 [Fe(CN)6 ]4 nanocubes are grown in-situ on reduced graphene oxide (rGO) sheets, followed by thermal decomposition of the Sn3 [Fe(CN)6 ]4 /rGO precursor in an Ar/H2 atmosphere. As a result, the lithium-ion batteries based on FeSn2 /FeSn/Fe-rGO composites exhibit outstanding lithium storage performance with a remarkable reversible capacity of 1274 mAh g −1  at 0.2 A g −1 after 200 cycles, a great rate capability of 665 mAh g −1  at 5.0 A g −1, and excellent high-rate cycling stability with a capacity decay of only 0.025% per cycle within 1200 cycles at 2.0 A g −1 . The excellent electrochemical performance of FeSn2 /FeSn/Fe-rGO can be ascribed to its unique three-order buffer structures: the Fe atoms in FeSn2 and FeSn acting as tough buffer, metal Fe as framework buffer for cubic nanoparticles, and rGO as 2D elastic matrix buffer, which effectively alleviate the volume expansion and structural pulverization of the electrode during lithiation, synergistically enhance the lithium storage performance. Graphical abstract: Image 1 Highlights: Graphene supported Fe-Sn nanoalloy composites were prepared via a facile metal-organic framework precursor route. The FeSn2 /FeSn/Fe-rGO anode exhibits high reversible capacities, great rate capability, and excellent cycle stability. Fe species in the composites effectively alleviated the volume expansion and structural pulverization of the electrode. The graphene matrix accommodated the large volume change and prevented Fe–Sn alloy particles aggregation.